Thrombin and protease-activated receptors (PARs) in atherothrombosis - Martorell, Lluis; Martínez-González, José; Rodríguez, Cristina; Gentile, Maurizio; Calvayrac, Olivier; Badimon, Lina (Thrombosis and Haemostasis, 2008)
Thrombin is a multifunctional serine protease generated at the site of vascular injury that transforms fibrinogen into fibrin, activates blood platelets and elicits multiple effects on a variety of cell types including endothelial cells, vascular smooth muscle cells (VSMC), monocytes,T lymphocytes and fibroblasts. Cellular effects of thrombin are mediated by protease-activated receptors (PARs), members of the G protein-coupled receptors that carry their own ligand which remains cryptic until unmasked by proteolytic cleavage. Thrombin signalling in platelets contributes to haemostasis and thrombosis. In normal arteries PARs are mainly expressed in endothelial cells, while their expression in VSMC is limited. Endothelial PARs participate in the regulation of vascular tone, vascular permeability and endothelial secretory activity while in VSMC they mediate contraction, migration, proliferation, hypertrophy and production of extra-cellular matrix. PARs contribute to the pro-inflammatory phenotype observed in endothelial dysfunction and their up-regulation inVSMC seems to be a key element in the pathogenesis of atherosclerosis and restenosis. In the last years a myriad of studies have emphasized the critical role of PAR signalling in thrombin mediated effects in haemostasis, inflammation, cancer and embryonic development. Lately, PARs have become a therapeutic target to inhibit platelet aggregation and thrombosis. Early data from a clinical trial (TRA-PCI) to evaluate safety and efficacy of a potent new oral thrombin receptor antagonist (TRA) have promisingly indicated that overallTRA treatment reduces adverse event rates without an increase in bleeding risk. In this paper we review cellular responses triggered by thrombin and their implication in vascular pathophysiology.
Keywords: Atherothombosis; thrombin; protease-activated receptors; gene expression